Characterization of a room temperature predictable quantum efficient detector for applications in radiometry and photometry. (27th July 2018) - Salffner, K; Dönsberg, T; Porrovecchio, G; Smid, M; Nield, K; Nevas, S
Abstract: This paper presents the experimental characterization of predictable quantum efficient detectors, which have been designed for use at room temperature. The aim of the characterization was to validate modelled properties experimentally and, thus, the feasibility of such room temperature predictable quantum efficient detectors to be used as primary radiometric standards for applications in the fields of photometry and radiometry with an aimed uncertainty level of 0.01 . The characterizations were focused on linearity, thermal, angular, spectral and polarization dependencies of the detector that need to be known and considered in the respective applications. The results of the characterization measurements confirm the predictability of the detector, within the aimed 0.01 uncertainty level and, thus, the high potential for using that kind of devices as primary standards for applications in radiometry and photometry.